The Effect Of Macroeconomics On Ten Sectoral Stock In-dices For The Period 2011-2020 (Jasica-Index) - Yusril Arifando, Fahmi; Adib, Noval (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to analyze the effect of macroeconomic factors partially and simultaneously on the sectoral stock price index listed on the Indonesia Stock Exchange. This study's independent macroeconomic variables are GDP rate, inflation, and Rupiah / USD exchange rate. The dependent variable used is the ten IDX sectoral index stock prices. The model used in this research is Ordinary Least Squares with the help of SPSS software. The data used in this study are quarterly and time series data from 2011 to 2020, with 40 observations. The data in this study were obtained from the Central Bureau of Statistics, Bank Indonesia, and Investing.com. The results show that GDP and inflation do not affect the ten sectoral stock indices. The Rupiah exchange rate negatively and significantly affects nine sectoral stock price indices except the mining sector index. Simultaneously, GDP, Inflation, and the Rupiah Exchange Rate significantly affect all ten sectoral stock price indices, except the mining sector.